2005
DOI: 10.1007/s10657-005-1735-0
|View full text |Cite
|
Sign up to set email alerts
|

Negotiated Third Party Access—An Industrial Organisation Perspective

Abstract: In the course of the liberalization of European energy markets, the German government opted-diverging from all other European countries-for Negotiated Third-Party Access. In this article we analyze if, theoretically, this institutional regime can be superior to regulation. We review empirically whether certain aspects of the actual implementation, in particular publication of the network access charges for each network supplier, facilitated or inhibited competition. In the first place we reconsider previous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It is unclear whether the changes are representative for the sector. Growitsch & Wein [2004] calculate a reduction of the spread in network charges among various operators as a result of the introduction of the self-regulation in VV II+ 15 . This suggests that the increases by some are levelled out by decreases by others.…”
Section: Past Present and Futurementioning
confidence: 99%
“…It is unclear whether the changes are representative for the sector. Growitsch & Wein [2004] calculate a reduction of the spread in network charges among various operators as a result of the introduction of the self-regulation in VV II+ 15 . This suggests that the increases by some are levelled out by decreases by others.…”
Section: Past Present and Futurementioning
confidence: 99%
“…In other words, if a high-priced network is not able to justify the high level it will find itself in the spotlights of the Cartel Office. Growitsch & Wein (2004) observe that this reduced the spread in network charges.…”
Section: Cost-based or Price-based Regulation?mentioning
confidence: 84%
“…Retail margins were also low and the author's recommendation is that the regulator should control access prices in order to increase competition. Growitsch and Wein (2005b) found that at the low voltage level, access charges set by vertically integrated firms were lower than the ones set by independent suppliers. However, companies are obliged to give details of the access charges they apply, and according to the authors, the consequences have been tacit collusions.…”
Section: Suppliers and Creditorsmentioning
confidence: 94%